Status of Educational Attainments Among Female Population in Haryana, India - Ishtiyaque, Mohammad; Anita,; Khan, Md. Israil; Jahan, Mussarat (National Geographical Journal of India, 2022)
Social indicators like religion, caste and creed become stronger indices when these are coupled with literacy and education to distinguish between inter and intra social groups. A social group with higher level of educational attainment is considered more active, productive and dynamic than those having low level of education. Higher education is regarded as an important factor to bring about socio-economic changes. Studies show that there exists a significant gap between male and female with regard to the level of education in the developing countries in which female literacy is found very low. The present case study of Haryana, a State adjacent to Delhi confirms the above statement. As per the census of India 1981, female literacy in the State was 22% against 48% for male population. The share of female literacy increased to 33% in 1991, 55% in 2001 and 67% in 2011; still lagging behind by 20% against the male population. It is also to be noted that Mewat District of Haryana registered only 38% female literacy against 73% among males. A general view about low literacy among female population in Haryana is due to cultural taboos. The society is divided into many Khaps – small cultural groups, which control social and cultural activities of the society. The Khaps do not allow much freedom to women acquire modern education and participate in development programmes. The paper highlights the status of educational attainment among women population in Haryana. In spite of the economically progressive State, the level of higher education among the female population is far behind the expectations or national average. Thus the objective of the paper is also to investigate the reasons behind such a low level of educational attainments among female population in Haryana. The study is based on secondary data derived from the census of India ranging from 1971 to 2011. Education index has been found out for each district separately to understand the district wise differences in educational level among the female population and to highlight the main reasons behind low level of education among them. The study may go a long way to the upliftment of higher education among Haryanavi women and help planners to achieve their goal in educational planning in the State.